Quantitative total reflection X‐ray fluorescence analysis of directly collected aerosol samples. (8th February 2017) - Prost, J.; Wobrauschek, P.; Streli, C.
Abstract : In this paper, the results of a feasibility study, investigating a new quantification method of directly collected aerosol samples, are shown. As sampling substrates, quartz reflectors suitable for total reflection X‐ray fluorescence analysis were used, and the spot patterns produced by a three‐stage Dekati impactor were considered. For calibration, the mentioned spot patterns were simulated on the surface of quartz reflectors using a self‐developed nanoliter deposition unit and multielement standard solutions. A droplet containing 5 ng of Y was applied in the center of each reflector and served as internal standard. Calibration standards and aerosol samples were prepared and analyzed in the same way. Linear calibration curves and good recovery rates were obtained. Aerosol samples were collected at the Atominstitut on quartz reflectors greased with petroleum jelly ('Vaseline'). The Vaseline layer is removed by cold‐plasma ashing, and afterwards, the internal standard is added. The samples can be then analyzed directly by total reflection X‐ray fluorescence without any further chemical pretreatment steps. As an application of the described method, two indoor and two outdoor samplings were carried out. In the investigated size range (>1 μm), mostly crustal elements were found and Ca values exceeded 100 ng/m 3 in the size fractions below 10 μm. Detection limits of around 10 pg/m 3 were achieved for medium Z elements (Fe to Sr) in the largest size fraction, whereas values for the two smaller stages typically lie between 30 and 100 pg/m 3 . Copyright © 2017 John Wiley & Sons, Ltd.